PENGARUH VARIASI STERN TUNNEL PADA PROPELLER TERHADAP EFISIENSI WAKE FRICTION - Nindi Utami Putri (2021)
In distributing basic needs to various regions and also traveling from one to another area, using a ship is an efficient and economical way. In order to achieve this, the ship must sail with good performance. To improve the performance of a ship, one of the things that can be done is to modify the hull of the ship. In this study, modification of the hull at the stern by adding variations of the stern tunnel to reduce the value of wake friction so that the thrust of the ship can increase. In that way it can increase the efficiency of the propeller. Wake that occurs on the ship can be caused by the influence of the hull itself, where the fluid will flow through the hull from the bow to the stern by forming a flow. The research was conducted by making a hull design with the Maxsurf Modeller, then modifying the hull model at the stern with stern tunnel variations, after that analyzing the four models that have been made on the value of resistance and wake friction using CFD-based software, called Ansys CFX. From the addition of stern tunnel, the resistance can be reduced by 25,4% and wake friction by 17,3%. It proves that the addition of a stern tunnel on a ship's hull can increase the efficiency of the ship.